MATRYCA INTERTEKSTUALNA POEMATU DRAMATYCZNEGO KASANDRA ŁESI UKRAINKI - Reda, Marta; Reda, Marta (Волинський національний університет імені Лесі Українки, 2008)
Автор статьи, анализируя поэтическую драму Леси Украинки “Кассандра”, обращает внимание на интересные интертекстуальные связи, которые украинская писательница вплела в текст своего произведения. Использованный Лесей Украинкой потенциал антической мифологии − миф о падении Трои − послужил интертекстуальной матрицей, которую поэтесса трансформировала соответственно собственной интерпретации, учитывая при этом тенденции в поэтике модернизма, а также обращаясь к другим культурным текстам и литературным дискурсам. Analyzing Lesya Ukrainka’s poetical drama „Kassandra”, the author of the present paper pays attention to very interesting intertectual references, which Ukrainian poetess introduced in the outline of the text. Using antique mythology, that is the myth about Troy’s fall, as the intertectual matrix, Lesya Ukrainka transformed it according to her own interpretation, taking into consideration the tendencies appearing in the poetics of modernism, addressing other cultural texts and literary discourses as well.
Matryca intertekstual’na dramatic poemi of Kassandra of Lesi Ukrainian
Keywords: матрица; matrryca; драма „Кассандра”; drama „Kassandra”; античная мифология; ancient mythology; поэтика модернизма; poetics of modernism